Six-month color change and water sorption of 9 new-generation flowable composites in 6 staining solutions - Maria ARREGUI; Luis GINER; Marco FERRARI; Marta VALLÉS; Montserrat MERCADÉ
Abstract Color match and water sorption are two factors that affect restorative materials. Discoloration is essential in the lifespan of restorations. The aim of this study was to evaluate color change and water sorption of nine flowable composites at multiple time points over 6 months. 60 samples of each composite were divided into two groups (Color Change and Water Sorption/Solubility). Each Color Change group was divided into six subgroups, which were immersed in distilled water (DW), coffee (CF), Coca-Cola (CC), red wine (RW), tea (TE) and orange juice (OJ). The color was measured at the baseline, 1, 2, 3 and 4 weeks, and 3 and 6 months and color change values (ΔE) were calculated. Each Water Sorption [WS]/Solubility [WL] group was tested according to ISO 4049:2009. The data were evaluated using two-way ANOVA, Fisher's post-hoc test and Pearson's correlation test. The composite with the lowest ΔE differed for each solution: Filtek™ Bulk Fill in DW (∆E = 0.73 (0.17-1.759)); Vertise Flow in CF (∆E = 14.75 (7.91-27.41)), in TE (∆E = 7.27 (2.81-24.81)) and OJ (∆E = 3.17 (0.87-9.92)); Tetric EvoFlow® in CC (∆E = 1.27 (0.45-4.02)); and Filtek™ Supreme XTE in RW (∆E = 8.88 (5.23-19.59)). RW caused the most discoloration (∆E = 23.62 (4.93-51.36)). Vertise Flow showed the highest water sorption (WS = 69.10 ± 7.19). The Pearson test showed statistically significant positive correlations between water sorption and solubility and between water sorption and ∆E; the positive solubility-∆E correlation was not statistically significant. The findings suggest that water sorption is one factor associated with the ability of composites to discolor; however, discoloration is a multifactorial problem.